The water's edge - Fossum, Karin, 1954- (Fossum, Karin, 1954- Inspector Sejer mystery., 2009)
"A married couple, Reinhardt and Kristine Ris, are out for a Sunday walk when they discover the body of a boy and see the figure of a man limping away. They alert the police, but not before Reinhardt, to Kristine's horror, kneels down and takes photographs of the dead child with his cell phone. Inspectors Konrad Sejer and Jakob Skarre begin to make inquiries in the little town of Solberglia. But then another boy disappears, and an explanation seems more remote than ever. Meanwhile, the Ris's marriage starts to unravel as Reinhardt becomes obsessed with the tragic events and his own part in them" -- from publisher's web site.